“Estrategias lúdicas para el aprendizaje de Ciencias Naturales” - Rojas Tapia, Cecilia Jacqueline (2021)
Teaching-learning process is the stage where teacher uses various teaching strategies to support their selves, guide the student in their learning. Against this, playful strategies represent an important stimulus in learning, when children play, at the same time they are learning, experimenting and discovering their environment. In the same way, these allow to the student to strengthen their integral development either alone or with their peers. In this sense, the objective of this research was to propose playful strategies through a methodological guide for learning improvement in the area of Natural Sciences. Therefore, used methodology was qualitative research because it describes aspects of the subject to be investigated, based on four stages such as: preparatory, field work, analytical and informative. In addition, the interpretive approach was applied because it allows to understand and study the reality of the educational fact, through the use of the observation technique and the observation guide instrument that allowed to collect information from teaching-learning process. In this way, the research contributed with a playful strategy guide, where sequential stands are developed with topics related to Natural Sciences area to stimulate teaching-learning process, achieving active participation, trust and autonomy of the students. . As such, it is concluded that the application of playful strategies in didactic process develop motivation and creativity as elements for students to awaken interest in learning. Likewise, it helps to the student to create mental schemes for meaningful learning construction, and in turn be responsible for their own learning. On the other hand, teaching competence of teacher changes in a positive way because they assume a new guide role, learning facilitator and mediator.